SOLUSI DAKWAH DALAM MENYIKAPI PROBLEMATIKA EKONOMI MASYARAKAT KONTEMPORER - Faridah Faridah; Rahmatullah Rahmatullah; Muhammad Yusuf (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2021)
This paper describes the solution to da'wah in addressing the economic problems of contemporary society. Da'wah as a means or way in conveying religious teachings should understand the condition of the people, understand the causes of poverty suffered by the people which consists of three factors, namely individual cultural psychological factors, structural factors and inherited or hereditary factors. The problem given is that the problem of poverty requires cooperation from various elements of society using religious, structural, da'wah, psychological, educational, economic and social approaches.